Pengaruh Kemiskinan Terhadap Tata Ruang Wilayah Perkotaan - Nurhidayah Nurhidayah (Rayhan Intermedia, 2021)
This article discusses the effect of poverty on urban spatial planning. Poverty and spatial planning in reality have a fairly close relationship, especially in determining the appearance of a city. As it is known that the emergence of sociological poverty is not only caused by economic factors, but also due to other factors. The factor in question is the failure to fulfill basic rights such as education, health, and so on. Actually, the process of poverty alleviation has become a routine agenda of government programs since the leadership of President Soekarno with the 8-Year National Development Program (Panasbede) until the era of President Joko Widodo's leadership with his magical programs: such as KIS, KIP, non-cash food assistance, and others.